2018
DOI: 10.1038/s41598-018-28989-4
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic transition from specialized root hairs to specific root-fungus symbiosis in the dominant Mediterranean seagrass Posidonia oceanica

Abstract: Terrestrial plants typically take up nutrients through roots or mycorrhizae while freshwater plants additionally utilize leaves. Their nutrient uptake may be enhanced by root hairs whose occurrence is often negatively correlated with mycorrhizal colonization. Seagrasses utilize both leaves and roots and often form root hairs, but seem to be devoid of mycorrhizae. The Mediterranean seagrass Posidonia oceanica is an exception: its adults commonly lack root hairs and regularly form a specific association with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…We found that the Glomerellales , particularly a Colleotrichum species (SV10), was abundant in the lower 10 inches of leaf tissue and enriched on the leaves relative to other sample types. DSE, particularly members of the Pleosporales, have previously been observed associating with seagrasses (Borovec and Vohník, 2018; Gnavi et al, 2014; Panno et al, 2013; Torta et al, 2015; Vohník et al, 2015, 2016, 2017, 2019). In the mediteranean seagrass, Posidonea , it has been observed that the abundance of the dominant root associated fungi, a Pleosporales species ( Posidoniomyces atricolor gen. et sp.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We found that the Glomerellales , particularly a Colleotrichum species (SV10), was abundant in the lower 10 inches of leaf tissue and enriched on the leaves relative to other sample types. DSE, particularly members of the Pleosporales, have previously been observed associating with seagrasses (Borovec and Vohník, 2018; Gnavi et al, 2014; Panno et al, 2013; Torta et al, 2015; Vohník et al, 2015, 2016, 2017, 2019). In the mediteranean seagrass, Posidonea , it has been observed that the abundance of the dominant root associated fungi, a Pleosporales species ( Posidoniomyces atricolor gen. et sp.…”
Section: Discussionmentioning
confidence: 88%
“…In the mediteranean seagrass, Posidonea , it has been observed that the abundance of the dominant root associated fungi, a Pleosporales species ( Posidoniomyces atricolor gen. et sp. nov.), is associated with changes in root hair morphology and can form ecto-mycorrhizal-like structures suggesting a close seagrass-fungi symbiosis (Borovec and Vohník, 2018; Vohník et al, 2016, 2017, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most well described of these DSE associations is between the mediteranean seagrass, Posidonia oceanica, and its dominant root-associated fungus, Posidoniomyces atricolor. This Pleosporales member has been found associated with changes in root hair morphology and can form ecto-mycorrhizal-like structures (Vohník et al, 2016(Vohník et al, , 2017(Vohník et al, , 2019Borovec & Vohník, 2018). Here, although we isolated seven members of the Pleosporales, none appeared to be close relatives to Posidoniomyces atricolor.…”
Section: Discussionmentioning
confidence: 76%
“…Dark septate endophytes (DSE), particularly members of the Pleosporales within the Dothideomycetes (Figure 6), have been observed to form associations with several seagrass species (Panno et al, 2013;Gnavi et al, 2014;Vohník et al, 2015Vohník et al, , 2016Vohník et al, , 2017Vohník et al, , 2019Borovec & Vohník, 2018;Hurtado-McCormick et al, 2019). DSE are a morphological, not phylogenetic (e.g.…”
Section: Discussionmentioning
confidence: 99%